Endophytes in Lignin Valorization: A Novel Approach - Mattoo, Aroosa Jan; Nonzom, Skarma (Frontiers in Bioengineering and Biotechnology, 2022)
Lignin, one of the essential components of lignocellulosic biomass, comprises an abundant renewable aromatic resource on the planet earth. Although 15-40% of lignocellulose pertains to lignin, its annual valorization rate is less than 2% which raises the concern to harness and/or develop effective technologies for its valorization. The basic hindrance lies in the structural heterogeneity, complexity, and stability of lignin that collectively makes it difficult to depolymerize and yield common products. Recently, microbial delignification, an eco-friendly and cheaper technique, has attracted the attention due to the diverse metabolisms of microbes that can channelize multiple lignin-based products into specific target compounds. Also, endophytes, a fascinating group of microbes residing asymptomatically within the plant tissues, exhibit marvellous lignin deconstruction potential. Apart from novel sources for potent and stable ligninases, endophytes share immense ability of depolymerizing lignin into desired valuable products. Despite their efficacy, ligninolytic studies on endophytes are meagre with incomplete understanding of the pathways involved at the molecular level. In the recent years, improvement of thermochemical methods has received much attention, however, we lagged in exploring the novel microbial groups for their delignification efficiency and optimization of this ability. This review summarizes the currently available knowledge about endophytic delignification potential with special emphasis on underlying mechanism of biological funnelling for the production of valuable products. It also highlights the recent advancements in developing the most intriguing methods to depolymerize lignin. Comparative account of thermochemical and biological techniques is accentuated with special emphasis on biological/microbial degradation. Exploring potent biological agents for delignification and focussing on the basic challenges in enhancing lignin valorization and overcoming them could make this renewable resource a promising tool to accomplish Sustainable Development Goals (SDG’s) which are supposed to be achieved by 2030.